2015
DOI: 10.1073/pnas.1514665112
|View full text |Cite
|
Sign up to set email alerts
|

Filling constraints for spin-orbit coupled insulators in symmorphic and nonsymmorphic crystals

Abstract: We determine conditions on the filling of electrons in a crystalline lattice to obtain the equivalent of a band insulator-a gapped insulator with neither symmetry breaking nor fractionalized excitations. We allow for strong interactions, which precludes a free particle description. Previous approaches that extend the LiebSchultz-Mattis argument invoked spin conservation in an essential way and cannot be applied to the physically interesting case of spin-orbit coupled systems. Here we introduce two approaches: … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
235
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(258 citation statements)
references
References 31 publications
(60 reference statements)
11
235
0
Order By: Relevance
“…This extends previous results for purely electronic systems [24][25][26][27][28] to Kondo lattices. At intermediate J K , glide symmetry is spontaneously broken, leading to a partially Kondo screened insulator (PKSI), where the hybridization between local moments and conduction electrons is modulated within the unit cell while preserving the translational symmetry of the SSL.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…This extends previous results for purely electronic systems [24][25][26][27][28] to Kondo lattices. At intermediate J K , glide symmetry is spontaneously broken, leading to a partially Kondo screened insulator (PKSI), where the hybridization between local moments and conduction electrons is modulated within the unit cell while preserving the translational symmetry of the SSL.…”
supporting
confidence: 89%
“…For ν = 4p + 4 [21], both the Fermi volume and the generalized invariant vanish and these constraints do not apply. Although spin-orbit coupling (SOC) is challenging to treat using flux insertion, if we apply existing results [24,26,27] on filling-enforced semimetals to the hybridized bands at these fillings our results remain unchanged if timereversal symmetry is present. There is then also the additional interesting possibility that the PKSI may be a topological Kondo insulator, as topological insulators can emerge naturally from filling-enforced SOC semimetals…”
Section: /2mentioning
confidence: 78%
See 1 more Smart Citation
“…angle resolved photoemission spectroscopy, but also because many physical phenomena originate only from states around E F. We have applied recently reported theory (refs. [32], [33]) to Dg33, Dg43 and Dg45 groups and found that the number of electrons in valence states of a material must be 8n+4 per unit cell, where n is a positive integer, in order to be a zero-gap semiconductor. This is a necessary condition for PY & CC states to touch exactly at E F and that no other bands cross the Fermi level.…”
Section: Ab Initio Search For Realistic Materialsmentioning
confidence: 99%
“…This has been the case of all Dirac semimetals discovered so far. Below we show that a nonsymmorphic symmetry [29,[53][54][55][56][57][58][59][60][61] protects the crossing and with it the topological surface states.…”
Section: Introductionmentioning
confidence: 99%